Aproximación proteómica para el estudio de la variabilidad genética y la respuesta a estrés en Quercus ilex L. subsp. ballota (Desf.) Samp. (IV Congreso Forestal Español, 2005)
Our research groups have just initiated a collaborative research project directed to studying variability among populations and responses to stresses in Quercus ilex L . by using a functional genomic approach. Our first experiments intended to analyze the leaf proteome by mean of two- dimensional gel electrophoresis for protein resolution, peptide analysis by mass spectrometry and protein identification by searching in protein or DNA databases. We have used leaves from adult trees and seedlings from different provenances. At the present we are carrying out studies of responses to water stress and pathogens. Results so far obtained and published support proteomics as an useful experimental approach in order to establish and characterize genetic variability among provenances and populations as well as to identify proteins and genes involved in responses to stresses.